Role of Value Added Tax in Total Tax Revenue: An Empirical Study of Nepal - Dahal, Ananta Raj (Journal of Population and Development, 2020)
This paper examines the role of Value Added Tax (VAT) in total tax of Nepal. Tax is the main sources of government revenue. There are different kinds of tax systems used in the world. The concept of VAT had been introduced in 1919 A D from Germany as a new concept of indirect tax system of the world. VAT system have introduced from 1995 A D in Nepal. The specific objectives are to analyse the trend of VAT and to examine the correlation between VAT with total revenue and total tax revenue in Nepal. This study is based on secondary data, which are incorporated from the Ministry of Finance and other related government as well as non-government organizations. Both analytical and descriptive statistics are applied as methods in this study. At the process of data analysis some statistical tools like regression, correlation, etc. are used. The study shows that VAT has significant percentage in total revenue and total tax revenue in Nepal. There are more than 99 present variations due to VAT in total revenue, total tax revenue and indirect tax revenue. All these relationship are significant as r >6 PEr everywhere. Thus, VAT has significant contribution in government revenue of Nepal. But the system of VAT must be improved to increase its effectiveness through the government policy level and increase awareness tax payers about baling system of VAT.